MODEL MAKE A MATCH UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Lisnawiza, Lisnawiza; Hafinda, Tengku; A. Rani , Samsuar (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2023)
This research aims to implementation of Make A Match learning model by giving rewards. This research uses a quantitative method with Pre-Experimental Designs. The research design used is Pre-Experiment One Group Pre-test Post-test Designs, in this design there is a Pre-test before and a Post-test after being given treatment. The research results showed that 62.825% were successful in implementing the Make A Match learning model with giving rewards, and 56.45% had an effect on students' interest in learning. Meanwhile, the pre-test and post-test results were based on the t-test with a significance level of ∝= 0.05, obtained t-test = 6.66 and t-table = 1.72. Because t-test > t-table, is 6.66 > 1.72, H0 is rejected, thus H1 is accepted. It can be concluded that there is an impact of the Make A Match learning model by giving rewards on the learning interest students. These results can be seen from the results of student achievements based on research conducted using data collection techniques both from the results of questionnaires and the results of the Pre-test Post-test. Keywords: Make A Match; learning model; reward